Tinjauan Perencanaan Trase Jalan KA Lintas Makassar Pare-Pare: Studi Kasus : Km. 71+900 - Km.73+600 - Sulistyo, Adi Nugroho (Program Studi Teknik Sipil Universitas Bosowa, 2023)
The construction of the Trans Sulawesi railway line phase 3, which began in 2019 across two regencies, namely Maros and Pangkajene and Islands regencies with a track length of 67.1 km. The Trans-Sulawesi railway line which was built in phase 3 is divided into two segments, the first segment crosses Maros district between km 14+400 to km 44+100, while the second segment crosses Pangkajene and Islands districts between km 44+100 to km 73+600 . The railway line that crosses Pangkajene and Islands regencies along 29.5 km crosses various regional conditions such as residential areas, plantations, rice fields, rivers, roads, hills and valleys. Based on these conditions, the condition of the vertical alignment on this line has a steep condition because it passes through hills and valleys which allows the train speed on the line to be low and not in accordance with the operating speed. For this reason, this research review aims to find other alternative routes by redesigning the route so that the train speed can match the planned speed, because on time schedule is one indicator of train scheduling performance